Acute exercise and motor memory consolidation: Does exercise type play a role? - Thomas, R.; Flindtgaard, M.; Skriver, K.; Geertsen, S. S.; Christiansen, L.; Korsgaard Johnsen, L.; Busk, D. V. P.; Bojsen-Møller, E.; Madsen, M. J.; Ritz, C.; Roig, M.; Lundbye-Jensen, J. (Scandinavian Journal of Medicine & Science in Sports, 2017)
A single bout of high-intensity exercise can augment off-line gains in skills acquired during motor practice. It is currently unknown if the type of physical exercise influences the effect on motor skill consolidation. This study investigated the effect of three types of high-intensity exercise following visuomotor skill acquisition on the retention of motor memory in 40 young (25.3 ±3.6 years), able-bodied male participants randomly assigned to one of four groups either performing strength training (STR), circuit training (CT), indoor hockey (HOC) or rest (CON). Retention tests of the motor skill were performed 1 (R1h) and 24 h (R1d) post acquisition. For all exercise groups, mean motor performance scores decreased at R1h compared to post acquisition (POST) level; STR (P = 0.018), CT (P = 0.02), HOC (P = 0.014) and performance scores decreased for CT compared to CON (P = 0.049). Mean performance scores increased from POST to R1d for all exercise groups; STR (P = 0.010), CT (P = 0.020), HOC (P = 0.007) while performance scores for CON decreased (P = 0.043). Changes in motor performance were thus greater for STR (P = 0.006), CT (P < 0.001) and HOC (P < 0.001) compared to CON from POST to R1d. The results demonstrate that high-intensity, acute exercise can lead to a decrease in motor performance assessed shortly after motor skill practice (R1h), but enhances offline effects promoting long-term retention (R1d). Given that different exercise modalities produced similar positive off-line effects on motor memory, we conclude that exercise-induced effects beneficial to consolidation appear to depend primarily on the physiological stimulus rather than type of exercise and movements employed.